Chronic Cough in Adults: Make the Diagnosis and Make a Difference - Kaplan, Alan G. (Pulm Ther, 2019)
Chronic cough is common and impactful, frustrating both patients and clinicians. An empirical trial of therapy is often done with inhaled corticosteroids, but this practice should be replaced with attempting to make an accurate diagnosis. The three most common causes are upper airway cough syndrome, asthma, and gastroesophageal reflux disease (GERD), but there are often multiple causes involved. Minimal investigations after history, physical exam, travel history, and drug history include a chest radiograph and spirometry. Empirical trial of therapy with inhaled corticosteroids is reasonable if there is evidence of eosinophilic inflammation. Empiric therapy for GERD may also be reasonable in those with symptoms. Red flags should especially be considered an urgency to make the correct diagnosis.